Pengaruh Pengawasan Keuangan Daerah terhadap Efektivitas Pengelolaan Anggaran Pemerintah Daerah Kabupaten Belu - Paskalis Kurniawan Suri; Yohana F. Angi; Cicilia A. Tungga (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
This study aims to determine and explain the effect of regional financial supervision on the effectiveness of budget management of the Belu Regency Regional Government. The type of research used by researchers is quantitative research using primary data. This research was conducted at the Regional Financial and Asset Management Agency (BPKAD) of Belu Regency. The sampling technique used in this study was by distributing questionnaires. The data analysis techniques used in this study are data validity and reliability tests, simple linear regression analysis, classical assumptions, hypothesis testing and the coefficient of determination (R²) using the Statistical Package for Social Science 22.0 for windows (SPSS 22) analysis tool. The results of this study indicate that regional financial supervision affects the effectiveness of budget management at the Regional Finance and Asset Agency of the Belu Regency Government.